2019
DOI: 10.1111/jfcj.12134
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Judges’ Self‐Reported Experiences of Secondary Traumatic Stress

Abstract: Many judges experience occupation‐specific stress, such as secondary traumatic stress (STS), burnout, compassion fatigue, and vicarious traumatization. A content analysis of 762 judges’ open‐ended responses to a survey asking whether they had suffered from STS revealed that judges moderately experienced most types of stress. Some case types (e.g., family court) and some job aspects (e.g., gruesome evidence) were particularly stressful. Judges reported both positive (e.g., social support) and negative (e.g., di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This observation differs from another qualitative study examining STS in a broader population of judges attending a national judicial college. In this study, Edwards & Miller (2019) note that while 45% of judges reported symptoms of vicarious trauma during qualitative interviews, there was evidence of a few judges who denied the existence of secondary traumatic stress altogether, referring to it as "absurd" and evidence of "government scammers" or "extraordinarily weak minds" (p.14). It is possible that the juvenile and family court judges dealing with sex trafficking of minor cases may have different levels of understanding about trauma than those who preside over other more diverse courts, cases and populations.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This observation differs from another qualitative study examining STS in a broader population of judges attending a national judicial college. In this study, Edwards & Miller (2019) note that while 45% of judges reported symptoms of vicarious trauma during qualitative interviews, there was evidence of a few judges who denied the existence of secondary traumatic stress altogether, referring to it as "absurd" and evidence of "government scammers" or "extraordinarily weak minds" (p.14). It is possible that the juvenile and family court judges dealing with sex trafficking of minor cases may have different levels of understanding about trauma than those who preside over other more diverse courts, cases and populations.…”
Section: Discussionmentioning
confidence: 74%
“…The judicial strategies spontaneously offered during these interviews (e.g., exercise, utilizing social support, caseload mix, task-focused coping) are consistent with these practices that promote health and wellbeing (Osofsky, Putman, Lederman, 2008). Post-adjudication briefings would allow for processing of experiences with peers and/or professionals may provide a pathway toward active coping, but needs empirical testing to determine its efficacy (Edwards & Miller, 2019). Training in best practices for addressing the needs of children and youth exploited by commercial sex is indicated as there is evidence in the literature that receiving competency training is associated with lower levels of secondary traumatic stress (Ludick & Figley, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As described by Remen (1996), “the expectation that we can be immersed in suffering and loss daily and not be touched by it is as unrealistic as expecting to be able to walk through water without getting wet” (p.52). Although a search of the literature revealed little on the impact of trauma and vicarious trauma on FMHEs, there is substantial research about vicarious trauma among mental health professionals (Bonach & Heckert, 2012) and legal professionals (Edwards & Miller, 2019; James, 2020; Leclerc et al, 2020), concluding that both groups experienced high rates of vicarious trauma. Referring to legal professionals, James (2020) addressed how ongoing stigma leads to “psychological dishonesty” and the denial of emotional difficulties.…”
Section: Applying Trauma-informed Principles To Forensic Mental Healt...mentioning
confidence: 99%
“…We define trauma as an “emotional response to a terrible event like an accident, rape or natural disaster” (American Psychological Association, 2020) typically including intrusive symptoms, avoidance symptoms, negative alterations to cognitions, and significant alterations in arousal and reactivity (American Psychiatric Association, 2013). “Secondary” or “vicarious” trauma, with similar symptoms, can occur when a person witnesses or is aware of terrible events even if they are not personally threatened with physical harm (Cieslak et al, 2013; Edwards & Miller, 2019). High levels of stress are implicated in various physiological conditions as well as producing disruptions in memory, concentration, and decision-making (Yaribeygi et al, 2017).…”
Section: Judicial Officer Studiesmentioning
confidence: 99%